Association of CYP2A6 Genetic Polymorphism and Lung Cancer in Female Never Smokers - R.A Henny Anggriani; Noni Novisari Soeroso; Setia Putra Tarigan; Putri Chairani Eyanoer; Hidayat Hidayat (Cell and BioPharmaceutical Institute, 2022)
Background: The major significant factor that affected lung cancer development among female passive smokers is environmental tobacco smoke. Nicotine can be found in a never smoker population, such as a child whose father is a smoker. Lung carcinogenesis in never smoker populations is affected by nicotine metabolism by CYP2A6 gene, which encodes the main nicotine metabolizing-enzyme. The aim of this study was to assess the genetic polymorphism of CYP2A6 and its association with secondhand smokers among females who have suffered from lung cancer in North Sumatra population.Materials and methods: This study was a case-control study, composed of 53 case subjects and 46 control subjects that were involved through a purposive sampling technique from two hospitals in Medan. PCR-RFLP was used for the examination of CYP2A6 gene to determine the genotype. The data were analyzed with conditional logistic regression test using Epi Info 7.0 software.Results: The most common genotype of CYP2A6 detected in this study was *1B/*1B (40.4%), while *1B allele had the highest prevalence (55.5%). There was no significant association between CYP2A6 genotype (p-value=0.61) or alleles (p-value=0.25) and the incidence of lung cancer.Conclusion: There was no association between CYP2A6 polymorphism and the incidence of lung cancer in secondhand smoker females.Keywords: CYP2A6, PCR-RFLP, female secondhand smokers, lung cancer